Can the 'post-national constellation' be re-constitutionalized - Dieter Grimm (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2004)
The constitutionalization of the state, the juridification of political power is one of the major achievements in the civilization of modern politics. Can and will this achievement survive the post-national constellation? The state no longer possesses all powers but some of its ruling authority has been transferred to non-state actors. Increasingly, regulations are the result of negotiations and agreements between state agencies and private parties. This, on the one hand, affects democratic legitimacy, since the parliaments are more and more sidelined. But these processes also undermine the rule of law. Such agreements evade the necessary formalization of law as they are rarely publicized. Nevertheless they are necessary to provide public goods. Globalization and internationalization further aggravate this problem. And the constitutionalization of international politics offers no ready-made solution for this problem: The WTO or even the EU both have to rely on the regular means of physical coercion still controlled by nation states. Even the EU is not a union of the people but of its member states, its democratic legitimacy is limited and, above all, its legalization and constitutionalization is rather circumscribed, and that can be attributed to the very same forces which also undermine democratic accountability at the state level. The aspiration expressed in the concept of constitutions and constitutionalization can, therefore, not even be approximately realized on the global level.
Keywords: 320; Verfassung; Staatsrecht; Souveränität; EU-Recht; EU-Staaten